EVALUATING THE EFFECTIVENESS OF TRAINING WITH THE KIRKPATRICK METHOD (STUDY OF SEMEN PADANG HOSPITAL EMPLOYEES) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
Services for patients in hospitals are very important to improve the quality of employee performance and provide maximum results related to service to patients. To improve the quality of this service it is necessary to conduct training of employees related to patient complaints. This study aims to evaluate the effectiveness of employee training at Semen Padang Hospital (SPH), using four levels of the Kirkpatrick evaluation model, which is to see the reaction or response of trainees to the training program, see the learning gained by the trainees, the behavior of trainees that is implied in their work and the results obtained for participants and companies after following the training. To determine the sample in this study using purposive sampling with the criteria for attending training in 2017-2018. The research methodology used in this study is the method of collecting survey data and questionnaires for Semen Padang Hospital employees who attended the training. Data analysis was performed using Microsoft Excel to process the questionnaire data and using SPSS 25.0 software to test Paired Sample t Test to see the comparison between before and after the participants attended the training more effectively as well as data obtained from Semen Padang Hospital (SPH). The results of the study found that the four level hypothesis used has a significant impact on the training program using instructors using training methods that are appropriate to the training being held, increased knowledge and competence of participants and can apply it to the work that it does. Evaluation of the reaction, learning, behavior and results of the training participants have a significant and effective effect on the effectiveness of the training.